2020
DOI: 10.1021/acs.analchem.0c02176
|View full text |Cite
|
Sign up to set email alerts
|

Open Space Diffusive Filter for Simultaneous Species Retrieval and Separation

Abstract: We present a novel method for the local retrieval of surface bound species and their rapid in-line separation using an open space microfluidic device. Separation can be performed in less than 30 s using the difference in diffusivities within parallel microfluidic flows. As a proof-of-principle, we report the rapid and efficient filtration of polystyrene beads from small molecules and surface bound red blood cells from dimethyl sulfoxide for antigen typing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…By controlling the relative position of the microfluidic probe and cells, the chemical microflow (central phase) was applied to target subcellular regions of single cells for chemical stimulation with the desired duration, which could controllably trigger in-depth cell behaviors for further analysis. The spatial precision of chemical treatment has been significantly higher than the presented results of existing works, and the method is obviously more general and practical than stimulation by reactive intermediates, enabling subcellular stimulation by common chemical species. Overall, the method is relatively general, easy to operate, and compatible with usual cell culture, chemical treatment, and analysis procedures, which do not require expensive equipment.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…By controlling the relative position of the microfluidic probe and cells, the chemical microflow (central phase) was applied to target subcellular regions of single cells for chemical stimulation with the desired duration, which could controllably trigger in-depth cell behaviors for further analysis. The spatial precision of chemical treatment has been significantly higher than the presented results of existing works, and the method is obviously more general and practical than stimulation by reactive intermediates, enabling subcellular stimulation by common chemical species. Overall, the method is relatively general, easy to operate, and compatible with usual cell culture, chemical treatment, and analysis procedures, which do not require expensive equipment.…”
Section: Discussionmentioning
confidence: 89%
“…Emerging open microfluidic probes can generate a leak-free reagent region for in situ cell stimulation. Even though continuous flow keeps the concentration distribution stationary, the rapid diffusion generates a diffusion layer over 15 μm wide, causing a concentration gradient , that poses difficulty in the precise focusing of chemical species. The reagent flow is usually over 100 μm wide and surrounded by a blurred boundary (15 μm thick diffusion layer), which could be used for single cell and half-cell , stimulation but is not suitable for further subcellular applications.…”
Section: Introductionmentioning
confidence: 99%
“…125 The authors demonstrated the use of height compensation to work with curved surfaces and tissue sections which are inherently non-planar. Some further applications include using parallel HFCs for diffusion based separation of surface bound species, 126 rapid sequential micro-immunohistochemistry 127 and multiplex analysis and quantitation in surface assays. 128…”
Section: Hydrodynamic Confinement Between Parallel Platesmentioning
confidence: 99%
“…"Open-space" microfluidics [21][22][23][24] has been used to provide excellent spatial resolution for micro-scale chemical sensing and patterning at biological surfaces, and diffusive transport phenomena. The technique operates under laminar conditions and must be close (10-100 mm distance) to a surface.…”
mentioning
confidence: 99%